Calcium signaling of in situ chondrocytes in articular cartilage under compressive loading: Roles of calcium sources and cell membrane ion channels. Issue 2 (3rd November 2017) - Lv, Mengxi; Zhou, Yilu; Chen, Xingyu; Han, Lin; Wang, Liyun; Lu, X. Lucas
ABSTRACT: Mechanical loading on articular cartilage can induce many physical and chemical stimuli on chondrocytes residing in the extracellular matrix (ECM). Intracellular calcium ([Ca 2+ ]i ) signaling is among the earliest responses of chondrocytes to physical stimuli, but the [Ca 2+ ]i signaling of in situ chondrocytes in loaded cartilage is not fully understood due to the technical challenges in [Ca 2+ ]i imaging of chondrocytes in a deforming ECM. This study developed a novel bi‐directional microscopy loading device that enables the record of transient [Ca 2+ ]i responses of in situ chondrocytes in loaded cartilage. It was found that compressive loading significantly promoted [Ca 2+ ]i signaling in chondrocytes with faster [Ca 2+ ]i oscillations in comparison to the non‐loaded cartilage. Seven [Ca 2+ ]i signaling pathways were further investigated by treating the cartilage with antagonists prior to and/or during the loading. Removal of extracellular Ca 2+ ions completely abolished the [Ca 2+ ]i responses of in situ chondrocytes, suggesting the indispensable role of extracellular Ca 2+ sources in initiating the [Ca 2+ ]i signaling in chondrocytes. Depletion of intracellular Ca 2+ stores, inhibition of PLC‐IP3 pathway, and block of purinergic receptors on plasma membrane led to significant reduction in the responsive rate of cells. Three types of ion channels that are regulated by different physical signals, TRPV4 (osmotic and mechanical stress), T‐type VGCCs (electrical potential), and mechanical sensitive ion channels (mechanical loading) all demonstrated critical roles in controlling the [Ca 2+ ]i responses of in situ chondrocyte in the loaded cartilage. This study provided new knowledge about the [Ca 2+ ]i signaling and mechanobiology of chondrocytes in its natural residing environment. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:730–738, 2018.